Optimalisasi Kualitas Pelayanan Perizinan Pada Dinas Penanaman Modal Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Ternate - Sukur Suleman; Rahmat Abd Fatah (Kolaborasi : Jurnal Administrasi Publik, 2021)
In the midst of the corona pandemic, the Investment Service and one-stop integrated services must minimize licensing service procedures, namely prioritizing the principles of e-governance and service task units as the central basis for the community in carrying out licensing services to avoid prolonged bureaucracy, but there are still problems and the community is sufficient feel that way. The purpose of this study is to examine the quality of licensing services at the Investment Service and one-stop integrated services in Ternate City. This research uses a qualitative approach with a type of case study. The data obtained through observation, interviews and documentation, as well as the analysis techniques used are the Milles and Huberman model, namely, data collection, data reduction, display data, verification, drawing conclusions. The results showed that the quality of licensing services at the Department of Investment and One-Stop Integrated Service (DPMPTSP) Ternate City was not optimal, it can be seen from the complaints of the public about the lack of innovation of officers in service implementation, transparency and accountability of services, procedures and customer satisfaction, and service facilities and infrastructure. The DPMPTSP of Ternate City should be creative or other alternatives either through the use of e-digital, providing special task units to the government in their respective regions so that the community is younger in processing permits. Keywords: optimization,  quality,  service,  licensing